Synergistic effects of insecticides and lactic acid bacterial formulation on Plutella xylostella (L.) and beneficial coccinellids in cauliflower - Jayaveni, M; Edward, Y S J T; Suganthi, A; Kannan, M; Anandham, R; Kannan, R; Rakesh, T (Plant Science Today, 2025)
India, a leading producer of cauliflower, experiences up to 52 % yield loss due to defoliating caterpillars, particularly Plutella xylostella (L.). Epiphytic lactic acid bacteria (LAB), known for their role in plant microbiomes, are widely used in agriculture as biofertilizers, biocontrol agents and biostimulants. In this note, the present study focuses on the co-application of LAB formulation with insecticides emamectin benzoate 05 % SG, tolfenpyrad 15% EC, chlorantraniliprole 18.5 % SC on potted cauliflower plants in a screenhouse over two seasons to combat P. xylostella and assess the orientation behaviour of predators, particularly coccinellids. The results showed that leaf area damage by P. xylostella was significantly reduced in plants treated with chlorantraniliprole 18.5 % SC + LAB (5 %) (63.39-66.17 %), compared to chlorantraniliprole 18.5 % SC (60.82-63.08 %) and LAB (5 %) alone (25.45-29.05 %). Coccinellid abundance was higher in plants treated with LAB (5 %) alone (1.98-3.03 per four plants) than in those treated with insecticides and control plots. LAB density of both seasons showed a similar trend, with significantly higher values in plants treated with LAB alone (45.17 CFU/cm²) and chlorantraniliprole 18.5 % SC (41.39 CFU/cm²), compared to control plants (1.88 CFU/cm²).